2019
DOI: 10.4293/jsls.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Resection in Laparoscopic Versus Robotic Transhiatal Esophagectomy

Abstract: Background and Objectives: As the use of robotic surgery continues to increase, little is known about robotic oncologic outcomes compared with traditional methods in esophagectomy. The aim of this study was to examine the perioperative oncologic outcomes of patients undergoing laparoscopic versus robot-assisted transhiatal esophagectomy (THE). Methods: Thirty-six consecutive patients who underwent laparoscopic and robot-assisted THE for malignant disease over a 3-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The pooled random effects result was an adjusted RD of 0.0 (95% CI, −0.03 to 0.03; I 2 = 5.4%) (Figure 3A). The RCT 24 and 5 unmatched observational studies 43,47,48,51,55 similarly showed no difference between approaches. Of the additional studies, a cervical anastomosis was used in 4 studies ( 3McKeown 24,43,51 ; 1 transhiatal 55 ).…”
Section: Anastomotic Leakmentioning
confidence: 92%
See 1 more Smart Citation
“…The pooled random effects result was an adjusted RD of 0.0 (95% CI, −0.03 to 0.03; I 2 = 5.4%) (Figure 3A). The RCT 24 and 5 unmatched observational studies 43,47,48,51,55 similarly showed no difference between approaches. Of the additional studies, a cervical anastomosis was used in 4 studies ( 3McKeown 24,43,51 ; 1 transhiatal 55 ).…”
Section: Anastomotic Leakmentioning
confidence: 92%
“…The RCT 24 and 5 unmatched observational studies 43,47,48,51,55 similarly showed no difference between approaches. Of the additional studies, a cervical anastomosis was used in 4 studies ( 3McKeown 24,43,51 ; 1 transhiatal 55 ). One study 47 was from a large database and compared robotassisted Ivor-Lewis with an unspecified transthoracic VAMIE, suggesting at least 1 study group had an intrathoracic anastomosis.…”
Section: Anastomotic Leakmentioning
confidence: 92%
“…Interestingly, the authors reported using biologic mesh to reinforce the hiatus to address the issue of postoperative diaphragmatic hernias, a step rarely performed today [27,41] . Others have also reported similar outcomes [84][85][86][87] . More recently, Wecowski et al [88] prospectively reported their experience in incorporating a robotic platform for transhiatal esophagectomy.…”
Section: Outcomes Of Robotic Esophagectomymentioning
confidence: 67%
“…There are currently a limited number of studies evaluating robotic transhiatal esophagectomies, none of which are randomized. Although some authors have reported similar oncologic results in robotic transhiatal resections compared to open (21,22), no study has reported PROs. Overall, further randomized perspective studies need to be performed to provide any definitive conclusions.…”
Section: Robotic Assisted Minimally Invasive Esophagectomy (Ramie) Versus Openmentioning
confidence: 99%